2022
DOI: 10.4103/jiaps.jiaps_334_20
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Urinary Biomarkers Neutrophil Gelatinase-Associated Lipocalin and Kidney Injury Molecule-1 as a Marker for Diagnosing the Presence of Renal Scar in Children with Vesicoureteral Reflux (VUR)

Abstract: Aim: To explore the possibility of using urinary biomarkers neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) to assess the presence of renal scars in children with Vesicoureteric Reflux (VUR). Materials and Methods: This cross-sectional study was conducted in 94 children aged 0–16 years diagnosed with VUR in the Department of Pediatric Surgery, JIPMER. Urinary biomarkers were measured using the enzyme-linked immunosorbent assay kits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Thus, contrary to the results reported by Amiri [2] and Eskandarifar [20], in the studies by Ichino [18], Nickawar [19], and Parmaksız [21], the uNGAL levels did not appear to reflect the severity of VUR. Parmaksız's results [1] were consistent with Naik's conclusions: the uNGAL values were higher in children with renal scars than in those without renal scars [22]. Unlike uNGAL, uKIM-1 and uKIM-1/Cr were not able to predict renal scar formation.…”
Section: Ngal As a Predictive Tool For Renal Scarring And Rnsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, contrary to the results reported by Amiri [2] and Eskandarifar [20], in the studies by Ichino [18], Nickawar [19], and Parmaksız [21], the uNGAL levels did not appear to reflect the severity of VUR. Parmaksız's results [1] were consistent with Naik's conclusions: the uNGAL values were higher in children with renal scars than in those without renal scars [22]. Unlike uNGAL, uKIM-1 and uKIM-1/Cr were not able to predict renal scar formation.…”
Section: Ngal As a Predictive Tool For Renal Scarring And Rnsupporting
confidence: 75%
“…Four original studies aimed specifically to assess the predictive value of uNGAL for the development of RN after they had already demonstrated the significant relationship between increased uNGAL and VUR [4,[21][22][23]. Apart from this, the correlation with the severity of VUR as well as a comparison with other biomarkers such as kidney injury molecule-1 (KIM 1) and liver-type fatty-acid-binding protein (L-FABP) was also sought.…”
Section: Ngal As a Predictive Tool For Renal Scarring And Rnmentioning
confidence: 99%
“…They also found that urinary NGAL concentrations were significantly higher in patients with VUR than in controls [20]. In their studies, Naik et al and Ganapathy et al also support the value of urinary NGAL in the diagnosis of RS [18,37].…”
Section: Discussionmentioning
confidence: 82%
“…Regarding RS detection, the studies suggest that higher concentrations of urinary NGAL were found in patients with VUR and RS compared with those with VUR without RS. Thus, NGAL may be a predictive biomarker for RN and its progression to ESKD [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly elevated creatinine-normalized urinary NGAL [26,27] and KIM-1 [28] and absolute urinary Cys-C [29] levels have been observed in UVR patients with renal scars compared to UVR patients with no renal scars. On the contrary, a few studies have reported no significant increases in creatinine-adjusted or absolute urinary KIM-1, NGAL [30], and Cys-C [31] in subjects with renal scars compared to those with no renal scars. In addition, significantly increased creatinine-normalized urinary NGAL, Cys-C [32], and KIM-1 [33] levels have been identified in subjects with urolithiasis, suggesting a potential role of these biomarkers in predicting associated renal injury.…”
Section: Discussionmentioning
confidence: 92%